Analyzing the Impact of Peak-Shaving on Load Reduction and on Battery Energy Storage System Degradation: A Simulation-Based Study in Husøy - Kournoutis, Georgios (UiT Norges arktiske universitet, 2023)
The island of Husøy, in Northern Senja, Norway, faces numerous voltage quality difficulties, which arise from the consequent surge in electricity demand by the local growing fishing industry. Collaborating with the local distribution system operator (DSO), Arva, the current study explores the implementation of Battery Energy Storage Systems (BESS) using a peak-shaving strategy to alleviate high-demand periods, aiming to make the grid more robust. Using the open-source tool SimSES as the modeling software, the research examines the strategy’s efficiency, focusing on load reduction during peak demand. Four main scenario cases were examined, each with a distinct peak-shaving threshold, to explore the system’s performance. Furthermore, this study pioneers a comprehensive degradation analysis of the BESS in Husøy, based on the four scenario cases, shedding light on its long-term lifetime patterns. Furthermore, additional simulation cases were designed to explore the impact of different State of Charge (SOC) levels, temperatures, and Li-ion battery technologies on the system’s longevity.